The effect of Kirkuk Oil Refinery on Air pollution of Kirkuk City-Iraq - Al-Dabbas, Moutaz; Ali, Lamyaa; Afaj, Adnan (Iraqi Journal of Science, 2024)
The total suspended particles (TSP) concentrations in air at Kirkuk Oil Refinery and the areas around was determined by using low volume air sampler (Sniffer) at selected locations in two periods October 2010 and March 2011. The results of average concentration of suspended particles (TSP) are higher than the permissible limits of the Iraqi National determinants of (350 μg/m3) and the world limits of (60-90 μg/m3) at the two periods: October 2010 (818.94μg/m3) and March 2011(956.8μg/m3). The little difference between the two periods reflects the little effect of the seasonal changes. Comparison of the averages of the heavy metals (Pb, Ni, Cr, and Cd) with the national and world limits, noticed that they are higher than these limits. Except for the concentration of Copper (Cu), at the two periods were lower than the world limits. These results represent the effect of meteorological factors on the air quality of the studied area. Consequently, the TSP and heavy metals pollutants concentrations for both sampling periods October 2010 and March 2011and the cumulative effects of both periods shown an increase at the direction away from the refinery mostly at the south east direction.